The Implementation of Basic Guidance Services in Selected Diocesan Catholic Schools in the Province of Antique - Genalyn E. Gipalen; Dennis V. Madrigal (Philippine Social Science Journal, 2020)
Guidance and counseling is a crucial concern today to aid the educational, vocational, and psychological potentials of the students for optimum achievement and adequate adjustment in the varied life situations. The primary purpose of a school's guidance and counseling program is to provide a broad spectrum of services to students, such as student assessment, the information service, placement and follow-up, and counseling assistance. Hence, this study intended to determine the extent of implementation of guidance services in Catholic schools in selected Diocesan Catholic Schools in Antique during the Academic Year 2019-2020. Likewise, it identified the challenges encountered by school personnel and students in implementing school guidance services. The study's findings were used as a baseline to develop a proposed program for the enhancement of the implementation of basic guidance services in Diocesan Catholic schools.